Phosphorylated B6 vitamer deficiency in SALT OVERLY SENSITIVE 4 mutants compromises shoot and root development. Issue 1 (3rd November 2021) - Gorelova, Vera; Colinas, Maite; Dell'Aglio, Elisa; Flis, Paulina; Salt, David E; Fitzpatrick, Teresa B
Abstract: Stunted growth in saline conditions is a signature phenotype of the Arabidopsis SALT OVERLY SENSITIVE mutants ( sos1 - 5 ) affected in pathways regulating the salt stress response. One of the mutants isolated, sos4, encodes a kinase that phosphorylates pyridoxal (PL), a B6 vitamer, forming the important coenzyme pyridoxal 5′-phosphate (PLP). Here, we show that sos4-1 and more recently isolated alleles are deficient in phosphorylated B6 vitamers including PLP. This deficit is concomitant with a lowered PL level. Ionomic profiling of plants under standard laboratory conditions (without salt stress) reveals that sos4 mutants are perturbed in mineral nutrient homeostasis, with a hyperaccumulation of transition metal micronutrients particularly in the root, accounting for stress sensitivity. This is coincident with the accumulation of reactive oxygen species, as well as enhanced lignification and suberization of the endodermis, although the Casparian strip is intact and functional. Further, micrografting shows that SOS4 activity in the shoot is necessary for proper root development. Growth under very low light alleviates the impairments, including salt sensitivity, suggesting that SOS4 is important for developmental processes under moderate light intensities. Our study provides a basis for the integration of SOS4 derived B6 vitamers into plant health and fitness. Abstract : Phosphorylated B6 vitamer content is decreased in salt overly sensitive4 mutant alleles, causing shoot and root developmental defects that are alleviated by growth under very low light.